Penerapan Mesin Pengasapan Ikan untuk Nelayan Desa Langkak Kecamatan Kuala Pesisir Kabupaten Nagan Raya - Muzakir Muzakir; Fitriadi Fitriadi; Iing Pamungkas; Khairul Hadi; Heri Tri Irawan; Arie Saputra; Rita Hartati (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
Fish is one of the species that is in high demand by consumers, including in Aceh. Fish can be obtained by catching from abundant nature. Problems in processing fish catches in Aceh, especially Langkak Village, Kuala Pesisir District, Nagan Raya Regency is a conventional post-capture processing method, which is drying using the heat of sunlight. In this condition, fish drying has several disadvantages, which are related to dependence on sunlight heat, cleanliness, freshness of fish, and selling points. For this reason, there needs to be a way to implement simple technology that uses a fish fogging machine. The purpose of carrying out this community service program is to provide practical applications of the fish fogging technique by providing soft skills to members of the fishing group in the Village of Langkak Village, Kuala Pesisir District, Nagan Raya Regency. The results of community service activities have been going well, starting with socialization activities or theory to the practice or application of fish fogging. The achievement of community service activities is the transfer of knowledge about making fish fogging machines and the practice and application of fish fogging directly by the fishermen of Langkak Village. In addition, other results are a manual guide on fish fogging to get the optimal fish fogging results. This activity received a good response from the fishermen of Langkak Village who participated in the activity, because it was considered very useful and became a facility to empower fishermen and residents in general.